Advanced engineering thermodynamics - Bejan, Adrian (Wiley, 2016)
Moving effortlerssly among analysis, essay and graphics, this streamlined edition of Adrian Bejan's powerful presentation is aimed at students in all areas of engineering, physics and life sciences.